Efektivitas Breastfeeding oxytocin massage chair BOMASIR - Septi Tri Rahayu; Alfirsta Auliyamatin Z; Zaenab Zahro Y; Ferry Martinda; Rizky Ridho Sembada; Ninuk Angelia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effectiveness of BOMASIR on respondents' comfort during the breastfeeding process. This type of research is a pre-experimental design with the one shot case study category. Samples were taken using the simple random sampling method, then analyzed using the SPSS software program. This research used a primary data collection method which was carried out on July 3 2024. Data was obtained through surveys and distributing questionnaires. The trial research was conducted at Integrated Service Post Toddler TemuGiring Pos 4 Sumbang, Banyumas, Central Java. Together with Sumbang Village Midwife Eka Wahyuningsih, A. Md. Kep and toddler Integrated Service Post cadres tested BOMASIR's innovation. The number of respondents in this study was 11 mothers participating in Posyandu Toddlers. Respondents were given 5 minutes to try the BOMASIR tool and fill out a questionnaire containing an assessment of the tool design and respondents' satisfaction with the BOMASIR tool on a Likert scale. The results of data analysis show that respondents gave very positive responses to the aesthetic appearance of BOMASIR innovation. Overall, the average percentage reached 98.7%, which is included in the